2023
DOI: 10.1080/16549716.2023.2213494
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the application of the 2009 Institute of Medicine gestational weight gain guidelines on pregnant Chinese women

Abstract: Background The 2009 Institute of Medicine (IOM) gestational weight gain (GWG) guidelines were initially developed for pregnant women in the United States. Objective This study aimed to investigate whether the IOM guidelines were suitable for pregnant Chinese women. Methods A retrospective cohort study comprising 20,593 singleton pregnant women was conducted at the Beijing Obstetrics and Gynaecology Hospital (1 January 2018 to 31 December 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…2 . Similar comparisons (based on nation-specific BMI criteria and IOM guidelines) have also been carried out in other studies [13] , [25] , [26] . In the present study, findings showed that overall, 62.78 % of subjects had gained inappropriate weight out of which nearly half of the subjects (48.12 %) had gained weight more than recommendations and 14.66 % subjects had gained less than recommended GWG limits.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…2 . Similar comparisons (based on nation-specific BMI criteria and IOM guidelines) have also been carried out in other studies [13] , [25] , [26] . In the present study, findings showed that overall, 62.78 % of subjects had gained inappropriate weight out of which nearly half of the subjects (48.12 %) had gained weight more than recommendations and 14.66 % subjects had gained less than recommended GWG limits.…”
Section: Resultssupporting
confidence: 53%
“…Hence, in the present study, the BMI criteria based on the Asian Indians (2009) [20] , was used to classify the pregnant women. Since, there are no national guidelines available for optimum GWG for obese and overweight Indian pregnant women, current study was aimed to assess the pattern of GWG w.r.t IOM guidelines-2009 among the subjects with BMI categories specified for (Asian-Indians,2009) as reported in earlier studies from China and India [13] , [25] , [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Even studies using the same statistical method recommend a completely different range of body mass, which may be related to the different inclusion outcomes. In terms of the outcome of the study, outcomes related to neonatal weight, such as SGA, LGA, low birth weight infants and macrosomia, are the most commonly used outcome indicators to calculate the range of weight gain during pregnancy, and pregnancy induced hypertension or preeclampsia are the most commonly used outcome indicators to minimize its risk [7,21,32,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…However, in view of the differences in race, environment, economic development level, medical service level, living habits, etc., the applicability of IOM 2009 GWG guidelines to pregnancy weight gain in other countries is controversial [7,[31][32][33]. This guideline has been demonstrated unsuitable for all Chinese women [34]. Many researches in different countries continued to explore appropriate gestational weight gain based on national data on pregnant women [31-33, 35, 36], and the statistical methods used and the GWG range recommended were also different.…”
Section: Introductionmentioning
confidence: 99%